2012
DOI: 10.1016/j.ijid.2011.09.013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of community-acquired pneumonia in children of Latin America and the Caribbean: a systematic review and meta-analysis

Abstract: The burden of CAP was substantial, with S. pneumoniae, H. influenzae, and M. pneumoniae being the most common pathogens identified. High quality primary studies on disease incidence, use of health resources, and standardized data collection on disease burden and circulating strains are essential to provide baseline data for the future evaluation of vaccine impact.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
19

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 56 publications
3
52
1
19
Order By: Relevance
“…Gentile et al (12) reported similar results, as pneumonia cases in their study occured mainly in infancy and early childhood under 2 years old. In the current study most of the cases were from urban areas of Egypt, which was smiliar to the results of FonsecaW et al (13) .…”
Section: Discussionsupporting
confidence: 65%
“…Gentile et al (12) reported similar results, as pneumonia cases in their study occured mainly in infancy and early childhood under 2 years old. In the current study most of the cases were from urban areas of Egypt, which was smiliar to the results of FonsecaW et al (13) .…”
Section: Discussionsupporting
confidence: 65%
“…When conducted on a mass scale, pneumococcal vaccinations had a significant effect on the risk of incidence and mortality from other serious invasive pneumococcal infections, such as sepsis, meningitis, or less serious non-invasive infections, such as otitis media (24,25).…”
Section: Discussionmentioning
confidence: 99%
“…Type 14 is a representative serotype conferring high invasive disease potential (9-11). It is also one of the most common etiologic agents of pneumonia in Latin America, the United Kingdom, and Spain and of otitis media in children under 5 years old (12)(13)(14). To further understand the basis for the distinct virulence profiles, we have also examined the nature of host innate immune responses elicited by these clinical isolates during the early stages of infection.…”
mentioning
confidence: 99%